2019
DOI: 10.1039/c9ra00350a
|View full text |Cite
|
Sign up to set email alerts
|

An efficient synthesis of new imidazo[1,2-a]pyridine-6-carbohydrazide and pyrido[1,2-a]pyrimidine-7-carbohydrazide derivatives via a five-component cascade reaction

Abstract: An easy synthesis of novel and highly substituted imidazo[1,2-a]pyridines and pyrido[1,2-a]pyrimidines using heterocyclic ketene aminals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This result, according to the authors, is due to the fact that when using polar solvents, the reaction is subject to kinetic control, while non-polar solvents contribute to the formation of structure 108, which is more thermodynamically favourable. L. Salhi et al [108] found that 2,3-diaminopyrimidine in the reaction with maleimides acts as a 1,3-N,N-dinucleophile, forming imidazo[1,2-a]pyridines with a wide range of biological activity [111][112][113][114]. As in [23], the authors suggested that the formation of 115 occurs first as a result of nucleophilic attack of the cyclic nitrogen atom of 2,3-diaminopyridine 110 of the double bond of maleimide 1.…”
Section: Reactions With Polynucleophilic Reagents and Involvement In ...mentioning
confidence: 99%
“…This result, according to the authors, is due to the fact that when using polar solvents, the reaction is subject to kinetic control, while non-polar solvents contribute to the formation of structure 108, which is more thermodynamically favourable. L. Salhi et al [108] found that 2,3-diaminopyrimidine in the reaction with maleimides acts as a 1,3-N,N-dinucleophile, forming imidazo[1,2-a]pyridines with a wide range of biological activity [111][112][113][114]. As in [23], the authors suggested that the formation of 115 occurs first as a result of nucleophilic attack of the cyclic nitrogen atom of 2,3-diaminopyridine 110 of the double bond of maleimide 1.…”
Section: Reactions With Polynucleophilic Reagents and Involvement In ...mentioning
confidence: 99%
“…Some commercial medications, such as zolpidem, necopidem, minodronic acid, and zolimidine, contain the core component imidazo[1,2-a]pyridine. [16] In recent years, a number of imidazo[1,2-a]pyridine-containing compounds have been described as prospective anticancer treatments, with imidazo[1,2-a]pyridines substituted at the C2 and C3 positions in particular demonstrating significant anticancer activity. [17,18] Imidazo [1,2-a]pyridines have anticancer efficacy by inhibiting CDK, VEGFR, PI3 K, EGFR, topoisomerase II, microtubulin protein, and other enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazo[1,2‐a]pyridines are also good indole and azaindole bioisosteres. Some commercial medications, such as zolpidem, necopidem, minodronic acid, and zolimidine, contain the core component imidazo[1,2‐a]pyridine [16] . In recent years, a number of imidazo[1,2‐a]pyridine‐containing compounds have been described as prospective anticancer treatments, with imidazo[1,2‐a]pyridines substituted at the C2 and C3 positions in particular demonstrating significant anticancer activity [17,18] .…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitous presence of heterocyclic systems containing one, two, three and four nitrogen atoms in five-membered ring viz; pyrrole [4][5][6][7][8], pyrazole [9][10][11][12], imidazole [13][14][15][16][17][18], etc. and the privileged systems containing two nitrogen atoms in a six-membered rings viz.…”
Section: Introductionmentioning
confidence: 99%